1990
DOI: 10.1029/wr026i007p01497
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy regression in hydrology

Abstract: A general methodology for fuzzy regression is developed and illustrated by an actual hydrological case study. Fuzzy regression may be used whenever a relationship between variables is imprecise and/or data are inaccurate and/or sample sizes are insufficient. In such cases fuzzy regression may be used as a complement or an alternative to statistical regression analysis. In fuzzy regression, several "goodness of fit" criteria may be used such as the maximum average vagueness criterion and the prediction vaguenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(82 citation statements)
references
References 8 publications
0
82
0
Order By: Relevance
“…The fact that transition is not sudden, reflects, similar to fuzzy set theory, the modeler's and observer's "degree of belief" (cf. Bárdossy et al, 1990) that a point belongs to a certain landscape unit, as shown in the illustrative example in Fig. 3.…”
Section: Hand-based Landscape Classificationmentioning
confidence: 99%
“…The fact that transition is not sudden, reflects, similar to fuzzy set theory, the modeler's and observer's "degree of belief" (cf. Bárdossy et al, 1990) that a point belongs to a certain landscape unit, as shown in the illustrative example in Fig. 3.…”
Section: Hand-based Landscape Classificationmentioning
confidence: 99%
“…Fuzzy numbers are an extension of fuzzy set theory, and express an uncertain or imprecise quantity. These types of numbers are particularly useful for dealing with uncertainties when data are limited or imprecise (Bárdossy et al, 1990;Guyonnet et al, 2003;Huang et al, 2010;Zhang and Achari, 2010) -in other words when epistemic uncertainty exists. This type of uncertainty is in contrast to aleatory uncertainty that is typically handled using probability theory.…”
Section: Fuzzy Numbers and Data-driven Modellingmentioning
confidence: 99%
“…Fuzzy numbers are an extension of fuzzy set theory [35] and express an uncertain or imprecise quantity. Fuzzy numbers are useful for dealing with uncertainties when data are limited or imprecise [36][37][38][39]. In this method, the model coefficients are defined to capture a predefined amount of observed data within different α-cut interval which are used to construct discretised fuzzy numbers.…”
Section: Fuzzy Artificial Neural Network For Risk Assessmentmentioning
confidence: 99%